2007
DOI: 10.1017/s0033291707009920
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal modeling of genetic and environmental influences on self-reported availability of psychoactive substances: alcohol, cigarettes, marijuana, cocaine and stimulants

Abstract: Background-We fitted ordinal latent growth models to measures of drug availability to determine the trajectories of genetic and environmental effects over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 88 publications
(113 reference statements)
1
29
0
Order By: Relevance
“…The use of retrospective data for the measurement of alcohol use has been utilized in many other studies [e.g., Gillespie et al, 2007; Schuckit et al, 2006] and been validated [Longnecker et al, 1992], but, in so far as some of our data are retrospective, it is a limitation. This limitation is somewhat ameliorated by the use of collateral reports of husbands’ and wives’ drinking.…”
Section: Discussionmentioning
confidence: 99%
“…The use of retrospective data for the measurement of alcohol use has been utilized in many other studies [e.g., Gillespie et al, 2007; Schuckit et al, 2006] and been validated [Longnecker et al, 1992], but, in so far as some of our data are retrospective, it is a limitation. This limitation is somewhat ameliorated by the use of collateral reports of husbands’ and wives’ drinking.…”
Section: Discussionmentioning
confidence: 99%
“…1, 2 are purely descriptive and call for further analysis in order to elucidate the possible underlying processes of developmental change in the effects of genes and environment on the patterns of twin resemblance within and between ages. The broad qualitative findings summarized above may arise from either or both of two different conceptions of how development proceeds (see Gillespie et al 2007). …”
Section: Methodsmentioning
confidence: 99%
“…It is conceivable, for example, that genetic influences account for individual differences in levels and rates of change, while autore-gressive effects account for the remembering or forgetting of time-dependent non-genetic influences. Efforts to combine the feature of autoregressive (Eaves et al 1986) with those from standard latent growth models (McArdle 1994; McArdle and Anderson 1989; McArdle and Hamagami 1991; Nesselroade and Baltes 1974), which are mathematically and statistically equivalent to random coefficient, multilevel or hierarchical linear models (Bryk and Raudenbush 1987; McArdle 1988; McArdle and Hamagami 1992; McArdle et al 1991; Mehta and West 2000; Miyazaki and Raudenbush 2000), have been applied to cognition (Finkel et al 2007; McArdle 1986) and drug availability (Gillespie et al 2007). One recent report has fitted a dynamic model to depression (Hishinuma et al 2012) but not within a genetically informative framework.…”
Section: Introductionmentioning
confidence: 99%
“…Summing results from these studies using meta-analytic techniques, they reported that for initiation of cannabis use, 48% of variance in liability in males and 40% of the variance in females could be attributed to additive genetic factors while the estimates for problematic cannabis use were 51% and 59%, respectively. Modest genetic influences on availability of cannabis have also been reported (Gillespie et al, 2007). …”
Section: Heritability Of Cannabis Use and Cannabis Use Disordersmentioning
confidence: 99%